Comparing and Predicting Rape Acknowledgment Between Sexual Orientation and Gender Identity Categories - Pugh, Brandie (Journal of interpersonal violence, 2025)
It is well known that sexual violence is a prevalent social problem that often results in numerous deleterious outcomes for victims and these outcomes are often influenced by rape acknowledgment (i.e., whether the rape victim acknowledges their experience as rape). Most research on rape acknowledgment examines acknowledgment as a dichotomous variable and comprises heterosexual cisgender women, revealing two gaps in the literature. To fill these gaps, this study used quantitative data that oversampled LGBTQ+ populations to examine three categories of rape acknowledgment (yes, no, uncertain) among a gender and sexually diverse sample (N = 817). Results indicate that 20% of the sample were uncertain as to whether they had been raped, 33% were unacknowledged victims, and 44% acknowledged their rape. Sexual minority transgender/nonbinary people had the highest prevalence of rape acknowledgment (56%), compared with four other groupings: heterosexual cis men and women as well as sexual minority cis men and women (28%–49%). Multivariate analysis revealed that when controlling for other factors, gender identity, but not sexual orientation, significantly predicts rape acknowledgment. Namely, sexual minority transgender/nonbinary people and cis women were more likely than cis men to acknowledge their rape. This study offers evidence to suggest that acknowledgment differs significantly by gender identity and is worth further inquiry. Limitations and suggestions for future research are discussed.